Heresy in the Roman Catholic Church: a history - Thomsett, Michael C. (McFarland, 2011)
"This book explains the construction and beliefs of the organized movements against the Roman Catholic Church and documents the individuals and their efforts in challenging papal infallibility, singular doctrine, and the Inquisition. It examines how heretics have never ceased to appear and reappear from ancient times into modern times"--Provided by publisher